National to local aid and recovery from extreme weather events evidence from the Philippines. - Abrigo, Michael (Economics working papers., 2019)
Findings show that the national government allocates more national aid and transfers during dry spells when damage is significantly higher and more prolonged than in periods of higher-than-usual precipitation. Yet, there is no significant link between national-to-local aid and local public finance and economic development to mitigate the adverse effects of extreme weather. The study uses local-level data on public income and expenditures, precipitation, poverty incidence, and satellite-based night-light luminosity.